TRACKING THE HISTORY OF EGYPT AS THE MIDDLE EAST: INITIERS AND CRITICS - Suwandi Suwandi; Komarudin Sassi (Program Pascasarjana UIN Sumatera Utara, 2024)
Egypt has played an important role in the history of the Middle East region from ancient times to the modern era. This research aims to trace the historical development of Egypt in the context of the region, with a focus on Egypt's contribution as an influential initiator of political, social and cultural thought in the Middle East as well as the emergence of criticism of Egypt's role from internal and external perspectives. Through historiographic analysis and primary source research, this research examines key periods such as the Ancient Pharaohs, the Islamic era, European colonialism, the rise of Egyptian nationalism, as well as Egypt's role in contemporary Middle Eastern politics. This research reveals that Egypt is not only the center of ancient civilization, but also continues to transform into a major power in the Middle East, both through modernist ideologies such as pan-Arabism, Nasserism, and as a major player in international relations in the region. However, Egypt's historical journey has also been marked by criticism from neighboring countries as well as internal groups regarding Egypt's policies on political and social issues. This research contributes to enriching the understanding of Egyptian history and its relevance in the dynamics of the Middle East, providing a new perspective on the relationship between Egypt as an initiator of change and a critic of its regional role.